Business model innovation – state of the art and future challenges for the field. (June 2014) - Spieth, Patrick; Schneckenberg, Dirk; Ricart, Joan E.; Spieth, Patrick; Schneckenberg, Dirk; Ricart, Joan E.
<x xml:space="preserve">Abstract</x> Business model innovation is receiving increased attention in corporate practice and research alike. We propose in this article a role‐based approach to categorize the literature and argue that the respective roles of explaining the business, running the business, and developing the business can serve as three interrelated perspectives to present an overview of the current business model innovation field and to accommodate the selected contributions of this special issue. We refer to contributions from entrepreneurship, innovation and technology management, and corporate strategy to explicate the three elaborated perspectives and to summarize the main contents of the special issue articles. We conclude by reflecting on main theoretical challenges for studies on business model innovation which stem from the uncertain boundaries of the phenomenon, and we propose some theoretical stances and analytic levels to develop future avenues for research.